2014
DOI: 10.1089/pho.2014.3756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Different Protocols of Low-Level Laser Therapy on Thyroid Hormone Production After Dental Implant Placement in an Experimental Rabbit Model

Abstract: Objective: The purpose of this study was to assess the systemic effects of low-level laser therapy (LLLT) on thyroid gland function and, consequently, calcium regulation -as measured by serum triiodothyronine (T3), thyroxine (T4), and free calcium levels -when administered after dental implant placement in a rabbit model. Background data: Protocols for the use of laser therapy in several clinical procedures are currently under investigation, as not all of the actions and systemic effects of laser irradiation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…High doses of potassium chloride exert cardiotoxic effects that quickly cause cardiac arrest, and its intravenous administration in unconscious animals or animals under general anesthesia is considered an acceptable procedure to induce cardiac arrest or death in animal experimentation. 21,22 All rabbits were in good nutritional status at the time of euthanasia.…”
Section: Lllt Protocolmentioning
confidence: 99%
“…High doses of potassium chloride exert cardiotoxic effects that quickly cause cardiac arrest, and its intravenous administration in unconscious animals or animals under general anesthesia is considered an acceptable procedure to induce cardiac arrest or death in animal experimentation. 21,22 All rabbits were in good nutritional status at the time of euthanasia.…”
Section: Lllt Protocolmentioning
confidence: 99%
“…Nonetheless, a growing number of observations suggests that specific wavelengths of electromagnetic radiation spanning the visible to near infra-red spectrum (400-1100nm) could lead to photo-physical and photochemical effects that can modulate major biological processes to achieve therapeutic goals such as cellular proliferation, mitochondrial function and inflammatory signalling (5) in various eukaryotic organisms, including humans. The majority of the literature reports the beneficial therapeutic effects of red and near infrared light (red: ~600-750, NIR: ~750-1100nm) in promoting tissue healing and reducing inflammation (6)(7)(8)(9)(10)(11)(12)(13)(14). Nevertheless, controversy still surrounds the application of PBM in practice, due to the lack of knowledge concerning how PBM elicits its molecular effects and also a poor understanding of photophysics and radiometric parameters which affect repeatability and reliability (15).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that LLLT did not protect the thyroid in different animals . On the other hand, other studies found that LLLT had a significant impact on serum T3 and T4, which differed by time and dose , these biomodulatory effects of laser may also occur remotely from the site of irradiation .…”
Section: Discussionmentioning
confidence: 99%
“…Low‐level laser therapy has been used for nearly 50 years to enhance tissue healing and to relieve pain, inflammation and swelling. Recently it has become apparent that LLLT can also be effective if delivered to normal cells or tissue before the actual insult or trauma, in a preconditioning mode . Although the mechanism of action of LLLT is still not fully understood, much information is now known concerning the short and long‐term effects of LLLT on cells and tissues .…”
Section: Discussionmentioning
confidence: 99%